A new approach in the context of ordered incomplete partial b-metric spaces - Tawseef Rashid (14548824) (2020)
The main purpose of this paper is to find some fixed point results with a new approach, particularly in those cases where the existing literature remains silent. More precisely, we introduce partial completeness, f̄-orbitally completeness, a new type of contractions and many other notions. We also ensure the existence of fixed points for non-contraction maps in the class of incomplete partial b-metric spaces. We have reported some examples in support of our results. Other information Published in: Open Mathematics License: http://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1515/math-2020-0054